Metal-algae interaction contributes to the water environment heterogeneity in an urbanized river. (June 2022) - Li, Di; Liu, Shiliang; Yang, Yuan; Guo, Li; Lyu, Bingyang; Yang, Rongjie; Zhang, Xiaoxia; Wang, Youlin; Yang, Fei; Chen, Qibing
Graphical abstract: Highlights: A comprehensive survey of water quality was performed in an urbanized river. Significant spatial–temporal heterogeneity of water environment was detected. Chrome and Cadmium affecting river water quality and algal structure. Nutrients and metals intrinsically aggravate the water environment. Abstract: The ecological environments of urban rivers are greatly affected by human activities, leading to serious water quality deterioration. We thus investigated urban aquatic environment and water pollution factors by collecting water samples over one year upstream, midstream and downstream of the Funan River in Chengdu, Sichuan, China. Measured water quality indicators included total N/P ratio, ammonia N, chemical oxygen demand, chlorophyll a, biochemical oxygen demand, transparency, turbidity, dissolved oxygen, conductivity, and pH, as well as the heavy metal concentrations and algal communities in the river sediments. Additionally, a water pollution index (WPI) and trophic level index (TLI) were calculated and a principal component analysis (PCA) was performed. The WPI analysis indicated serious pollution in this river during the sampling year. Moreover, moderate eutrophication with high pollution was found in summer (TLI = 64.7), while mild eutrophication occurred in the other seasons. The number of Cyanobacteria species sharply increased from 6 to 23 in summer, indicating a high risk of blooms. Furthermore, the PCA also revealed that two metals, chromium and cadmium, affected the water quality, which may be because of the interaction of nutrients and metals due to the land use types, industrial activities and hydrodynamic conditions. In general, we have systematically discussed the influences of various factors on the water environment and the mechanisms of their interactions in urbanized rivers, which is very important for the protection and restoration of river ecology as China and the world become more urbanized.